Anayasal bir kurum olarak milli güvenlik kurulu - Çınarlı, Gülden (My University, 2015)
ANAYASAL BİR KURUM OLARAK MİLLİ GÜVENLİK KURULU Dünyada ilk kez İkinci Dünya Savaşı sonrası hukuki bir kavram olarak kullanılmaya başlanmış milli güvenlik, kapsamı yorumlayan kişiye ve zamana göre değişen sınırlandırılamaz bir kavramdır. Milli Güvenlik Kurulu (MGK), 1961 Anayasası m.111’de ilk kez “milli güvenlik” gibi geniş bir alanda görev almak üzere oluşturulmuş; asker ve sivil üyelerden oluşan, Bakanlar Kurulu’na yardımcı, danışma nitelikli bir uzmanlar kuruludur. 1971 Anayasa Değişiklikleri ile gücünün artırıldığı kabul edilen Kurul, 1982 Anayasası m.118’de düzenlenen ilk şekliyle tarihteki en güçlü dönemini yaşamıştır. 2001 yılında Avrupa Birliği’ne uyum süreci kapsamında Anayasa’da yapılan değişikliklerde Kurulun görev alanı sınırlandırılmamış; sivil üyelerini artırmak ve kararlarının tavsiye niteliğinde olduğunu vurgulamakla yetinilmiştir. Anayasalarda hiçbir dönem icrai nitelik tanınmayan Kurul kararlarına ilişkin yapılan tartışmalar, MGK’nın uygulamada hukukun çizdiği sınırı aşarak hareket etmesinden kaynaklanmaktadır. venlik, İç Güvenlik, Dış Güvenlik, Ulusal Savunma, Milli Güvenlik Kurulu

THE NATIONAL SECURITY COUNCIL AS A CONSTITUTIONAL INSTITUTION The concept of national security which was first used as a legal concept after the Second World War is a concept of which scope cannot be limited and differs depending on the relevant person and period of time. National Security Council (NSC) is a committee of experts which was formed by civilian and military members as an advisory committee subordinated to the government, for the purpose of assuming duty within the framework of national security, which is a comprehensive concept, as stipulated by the article 111 of the 1961 constitution. The committee of which authority is accepted to have been increased through the amendments on the constitution that were enacted in the year 1971 has reached its most powerful state in history in its final form which has been prescribed by the article 118 of 1982 constitution. The amendments that have been made on the constitution in the year 2001 within the scope of the process of adaptation to the European Union haven’t limited the terms of reference of the committee but only increased the number of the committee civilian members and sufficed to state that the decisions of the committee have only a advisory nature. The discussions on the decisions of the committee, which have never been given an executive status, have arisen from the initiatives taken by NSC towards transgressing the limits set by the law in practice. National Security, Internal Security, Foreign Security, National Defense, National Security Council
Keywords: Anayasa; Dış Güvenlik; Hukuk; İç Güvenlik; Milli Güvenlik; Milli Güvenlik Kurulu; Türkiye; Ulusal Savunma